The influence of leveraged buyouts on target firms' competitors - Marcel Grupp; Christian Rauch; Marc P. Umber; Uwe Walz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
This paper analyzes the influence Leveraged Buyouts (LBOs) have on the operating performance of the LBO target companies' direct competitors. A unique and hand-collected data set on LBOs in the United States in the period 1985-2009 allows us to analyze the effects different restructuring activities as part of the LBO have on the competitors' revenues. These restructuring activities include changes to leverage, governance, or operating business, as well as M&A activities of the LBO target company. We find that although LBOs itself have a negative influence on competitors' revenue growth, some restructuring mechanisms might actually benefit competing companies.
urn:nbn:de:hebis:30:3-374441
Keywords: D43; G23; G24; G34; 330; Product Market Competition; Peers; LBOs; Restructuring